Salivary signatures of oral-brain communication in sleep bruxers - Deng, Yuwei; Zhu, Chenyuan; Jiang, Ruixue; Yu, Chunhua; Zhao, Jun; Jiang, Xinquan; Wen, Jin (Frontiers in Cellular and Infection Microbiology, 2023)
Microbiota and their interaction with hosts have been of great interest in brain research in recent years. However, the role of oral microbiota in mental illness and the underlying mechanism of oral-brain communication remains elusive. Sleep bruxism (SB) is an oral parafunctional activity related to the nervous system and is considered a risk factor for harmful clinical consequences and severe systemic conditions. In this study, salivary samples were collected from 22 individuals with SB and 21 healthy controls, and metagenomics with metabolomics was performed. Nonparametric Wilcoxon test were applied for the statistical analysis between the two groups.Microbial dysbiosis and altered oral metabolites were found in the SB individuals.The characteristic metabolite N-acetylglucosamine (GlcNAc) (VIP=8.4823, P<0.05) was correlated to a statistically lower Streptococcus mitis level in SB individuals.Salivary IFN-γ level and IFN-γ/IL-4 ratio were detected with significant changes in a chip assay. Amino acid metabolism pathways were upregulated, and the pathway with the largest number of differentially expressed genes is related to amino-tRNA charging pathway, while the most significantly enriched pathway is related to arginine biosynthesis. Neurotransmitter-associated pathways with glutamatergic and GABAergic synapses and cardiovascular system-related pathways were enriched in the SB group. Together, these results indicate a possible neuro-immune regulatory network of oral-brain communication in SB, which helps explain the mechanism of the oral microbiome with the host in sleep bruxers and provides a reference for early clinical and therapeutic intervention to improve the diagnosis and treatment of SB and similar diseases.